Short communication: Effects of Canarium indicum oil in enhancing brain-derived neurotrophic factor in rats - Hamidah Rahman; KUSNANDAR ANGGADIREDJA; TUTUS GUSDINAR; JOHNNER P. SITOMPUL; TURSINO TURSINO (Smujo International, 2020)
Abstract. Rahman H, Anggadiredja K, Gusdinar T, Sitompul JP, Tursino. 2020. Short communication: Effects of Canarium indicum oil in enhancing brain-derived neurotrophic factor in rats. Nusantara Bioscience 12: 168-174. The brain-derived neurotrophic factor (BDNF) is one of the neurotrophins family and plays an essential role during the development of neurons called neurogenesis. Since BDNF is critical for the function and survival of neurons, thus it represents the neuroprotective agent which useful in preventing neurodegenerative diseases. Here, we investigated BDNF serum concentrations after feeding the canarium oil (CO) and Canarium oil-based structured triglyceride (COST) in rats. Analysis of the BDNF serum was conducted by sandwich enzyme-linked immunosorbent assay (ELISA). The results demonstrated that the CO and the COST with the main composition of unsaturated fatty acids at the sn-2 position as much as 94.92% mol may enhance BDNF serum concentrations of up to 2.66% and 21.96% compared to the normal group of rats, respectively. This finding proves that the COST has prospects as an inducer of BDNF. However, further studies should be conducted to identify the precise dosage and safety products.